2005
DOI: 10.2166/wh.2005.0001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alternative on-site wastewater treatment on the viability and culturability of Salmonella choleraesuis

Abstract: The objective of this study was to determine how alternative on-site wastewater treatment systems (i.e. subsurface flow constructed wetlands, intermittent sand filters and intermittent peat filters) affect the viability and culturability of Salmonella choleraesuis (serotype typhimurium, ATCC 23567). Influent was a high strength septic tank effluent (BOD5 240-344 mgL(-1), TN approximately 100 mgL(-1), TP approximately 15 mgL(-1)) at the Natural Resources Research Institute's (NRRI) alternative treatment system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…DVC is based on a revitalization step of the food sample in the presence of a gyrase inhibitor (such as nalidixic acid and ciprofloxacin for Gram‐negative and Gram‐positive bacteria, respectively) blocking DNA synthesis and preventing cell division without affecting other metabolic activities of cells that thereby elongate, with an accumulation of ribosomes (and intracellular rRNA contents). DVC can then be followed by FISH so that by using specific rRNA‐targeted oligonucleotide probes viable cells of the target bacteria can be detected and enumerated (Pundsack and others ; Wu and others ; Moreno and others ).…”
Section: Current Trend and Future Perspectives In Milk‐ And Dairybornmentioning
confidence: 99%
“…DVC is based on a revitalization step of the food sample in the presence of a gyrase inhibitor (such as nalidixic acid and ciprofloxacin for Gram‐negative and Gram‐positive bacteria, respectively) blocking DNA synthesis and preventing cell division without affecting other metabolic activities of cells that thereby elongate, with an accumulation of ribosomes (and intracellular rRNA contents). DVC can then be followed by FISH so that by using specific rRNA‐targeted oligonucleotide probes viable cells of the target bacteria can be detected and enumerated (Pundsack and others ; Wu and others ; Moreno and others ).…”
Section: Current Trend and Future Perspectives In Milk‐ And Dairybornmentioning
confidence: 99%
“…In the indirect carbonation process mineral extraction is performed to increase the reaction rate between CO 2 and the cations, overcoming the limiting step in the direct carbonation process associated with the diffusion of the metal cations from the mineral lattice structure . Several mineral extraction mechanisms have been explored with varying challenges (mainly in terms of energy consumption and carbon footprint) dependent on the alkalinity source such as mechanical activation, , acid extraction, thermal activation, , and the patented ammonium sulfate activation …”
Section: Main Carbon Dioxide Conversion Productsmentioning
confidence: 99%
“…fecal coliforms and E. coli). Recently, demonstration projects performed near Duluth, Minnesota, at a cluster CW treatment system at Grand Lake and at replicate residential sized systems at the North East Regional Correction Center (NERCC) research site showed them to be effective in removing fecal coliforms year round, but with reduced efficiency in the winter (McCarthy et al 1998(McCarthy et al , 1999Axler et al 2001;Henneck et al 2001;Monson-Geerts et al 2001;Pundsack et al 2001Pundsack et al , 2005. Traditional bacterial indicators have come under intense scrutiny as indicator organisms for human pathogens because of their lack of correlation with levels of enteric viruses and their low survivability in aquatic environments (Goyal & Gerba 1983;Stetler 1984;Havelaar et al 1993;Ferguson et al 1996;Calci et al 1998;Leclerc et al 2001).…”
Section: Introductionmentioning
confidence: 99%